OPTIMALISASI PERAN NADZIR DALAM PENGELOLAAN DAN PEMANFAATAN WAKAF UNTUK PEMBANGUNAN GEDUNG MADRASAH (Studi Tk Al-Raudlatul Jadid Palengaan Pamekasan) - Adisah, Adisah; rohmah, wasilah (LPPM STAI Muhammadiyah Probolinggo, 2026)
Waqf is a sharia financial instrument that functions in the development of sharia economics, specifically in Muslim development, one of which is in Indonesia, precisely at the Miftahul Ulum Kebun Baru Islamic Boarding School foundation at the Al-Raudlahtul Jadid Kindergarten madrasah institution with a review of the management of nazhir in the management of waqf which includes the responsibilities of the nazhir. The method used is a descriptive qualitative approach with a type of field research. The results of this study are: 1.The sustainability and utilization of waqf depends heavily on the role of the nazhir. The nazhir is responsible for implementing various efforts necessary to safeguard and manage waqf assets to ensure their continued preservation and benefit. 2. Waqf at the Miftahul Ulum Kebun Baru Islamic Boarding School Institution is a productive waqf which is not only trustworthy, but must be professional in managing waqf assets, 3. Nadzir at the Al-Raudlahtul Jadid Kindergarten Institution here is a trustworthy and responsible nadzir, because the construction project is completed according to the time determined by the waqf fund provider.